Chatter stability analysis and prediction for elliptical ultrasonic vibration-assisted milling process - Li, Zhongqun; Yang, Shangzhen; Liu, Qiang; Liu, Hong; Liu, Yang (International journal of advanced manufacturing technology, 2024)
Elliptical ultrasonic vibration-assisted milling (EUVAM) introduces ultrasonic frequency vibration into conventional milling (CM) to achieve high-frequency intermittent milling. It has broad application prospects in processing difficult-to-cut materials such as titanium alloys, superalloys, carbon fiber-reinforced plastic (CFRP), and hard and brittle materials. This study focuses on the development of a dynamic model for EUVAM that considers regenerative effects and analyzes the interaction between the cutting edge and the workpiece in both radial and tangential directions, and the dynamic chip thickness is derived based on this model. To solve the model, a Runge-Kutta-based fully discrete method (RKFDM) is employed. This numerical method accurately predicts the stability of the EUVAM process under specified cutting conditions. In addition, a bisection algorithm is utilized to construct the stability lobe diagram of EUVAM, enhancing the computational efficiency of the process. Stability tests are conducted to validate the proposed stability model and solution method for EUVAM. The results of these tests confirm the accuracy and reliability of the approach presented in this paper. This study provides valuable insights and a practical framework for implementing EUVAM in the processing of difficult-to-cut materials, offering improved machining performance in various industrial applications.